Problem: Consider the equations below. (1) Ca (s) + CO2 (g) + 1/2O2 (g) → CaCO3 (s) (2) 2Ca (s) + O2 (g) → 2CaO (s) How should you manipulate these equations so that they produce the equation below when added: Check all that apply. CaO (s) + CO2 (g) → CaCO3 (s) (A) reverse the direction of equation (2) (B) multiply equation (1) by 3 (C) multiply equation (2) by 1/2

🤓 Based on our data, we think this question is relevant for Professor Hu's class at UNCG.

FREE Expert Solution
FREE Expert Solution
View Complete Written Solution
Problem Details

Consider the equations below. 

(1) Ca (s) + CO2 (g) + 1/2O2 (g) → CaCO3 (s) 

(2) 2Ca (s) + O2 (g) → 2CaO (s) 

How should you manipulate these equations so that they produce the equation below when added: Check all that apply. 

CaO (s) + CO2 (g) → CaCO3 (s) 

(A) reverse the direction of equation (2) 

(B) multiply equation (1) by 3 

(C) multiply equation (2) by 1/2